Keterampilan Prosedural dalam Menjawab Soal Matematika Peserta Didik Kelas 5 Sekolah Dasar - Inas Karima Rajab; Sandra Bayu Kurniawan (Didaktika Dwija Indria, 2026)
This study examined the correlation between procedural skills and ability to answer mathematics questions among 5th grade elementary school students. Specifically, it aimed to determine: (1) the level of students’ procedural skills; (2) the level of their ability to answer mathematics questions; and (3) whether procedural skills significantly contribute to students’ ability to answering mathematics questions. Using a quantitative correlational design, the study involved 62 5th grade students from three public elementary schools in Ngemplak sub-District, Boyolali Regency, selected through cluster random sampling. Data were collected using a 20-item procedural skills questionnaire and a 5-item essay test on fractions and plane geometry. Simple linear regression analysis revealed a strong and significant positive relationship between procedural skills and ability to answer mathematics questions (R = 0.893, R² = 0.798, F = 237.237 > F table, p < 0.001). The regression model Y = –29.892 + 1.332X indicated that procedural skills contributed 79.8% to the variance in students’ ability to answer mathematics questions scores. These findings suggest that students with higher procedural fluency demonstrate better mathematical accuracy and structured thinking. Theoretically, this reinforces the view that procedural mastery is essential for supporting effective mathematical reasoning. Practically, the results imply that teachers need to emphasize systematic step-by-step processes in mathematics instruction to strengthen students’ ability to answer questions at the elementary level.